Randomized Phase II Trial of Parsatuzumab (Anti‐EGFL7) or Placebo in Combination with FOLFOX and Bevacizumab for First‐Line Metastatic Colorectal Cancer. (April 2017) - García‐Carbonero, Rocío; van Cutsem, Eric; Rivera, Fernando; Jassem, Jacek; Gore, Ira; Tebbutt, Niall; Braiteh, Fadi; Argiles, Guillem; Wainberg, Zev A.; Funke, Roel; Anderson, Maria; McCall, Bruce; et al.
Abstract: Lessons Learned: These negative phase II results for parsatuzumab highlight the challenges of developing an agent intended to enhance the efficacy of vascular endothelial growth factor inhibition without the benefit of validated pharmacodynamic biomarkers or strong predictive biomarker hypotheses. Any further clinical development of anti‐EGFL7 is likely to require new mechanistic insights and biomarker development for antiangiogenic agents. Background: EGFL7 (epidermal growth factor‐like domain 7) is a tumor‐enriched vascular extracellular matrix protein that supports endothelial cell survival. This phase II trial evaluated the efficacy of parsatuzumab (also known as MEGF0444A), a humanized anti‐EGFL7 IgG1 monoclonal antibody, in combination with modified FOLFOX6 (mFOLFOX6) (folinic acid, 5‐fluorouracil, and oxaliplatin) bevacizumab in patients with previously untreated metastatic colorectal cancer (mCRC). Methods: One‐hundred twenty‐seven patients were randomly assigned to parsatuzumab, 400 mg, or placebo, in combination with mFOLFOX6 plus bevacizumab, 5 mg/kg. Treatment cycles were repeated every 2 weeks until disease progression or unacceptable toxicity for a maximum of 24 months, with the exception of oxaliplatin, which was administered for up to 8 cycles. Results: The progression‐free survival (PFS) hazard ratio was 1.17 (95% confidence interval [CI], 0.71–1.93; p = .548). The median PFS was 12 months for the experimental arm versus 11.9 months for the control arm. The hazard ratio for overall survival was 0.97 (95% CI, 0.46–2.1; p = .943). The overall response rate was 59% in the parsatuzumab arm and 64% in the placebo arm. The adverse event profile was similar in both arms. Conclusions: There was no evidence of efficacy for the addition of parsatuzumab to the combination of bevacizumab and chemotherapy for first‐line mCRC. The Oncologist 2017;22:375–e30